Exosomes Enhance Adhesion and Osteogenic Differentiation of Initial Bone Marrow Stem Cells on Titanium Surfaces - Lan, Yanhua; Jin, Qianrui; Xie, Huizhi; Yan, Chengxi; Ye, Yi; Zhao, Xiaomin; Chen, Zhuo; Xie, Zhijian (Frontiers in Cell and Developmental Biology, 2020)
Successful osseointegration involves the biological behavior of bone marrow stem cells (BMSCs) on an implant surface; however, the role of BMSC-derived extracellular vesicles (EVs)/exosomes in osseointegration is little known. This study aims to: (i) explore the interaction force between exosomes (Exo) and cells on the titanium surface, (ii) discuss whether morphology and biological behavior of BMSCs are affected by exosomes, and (iii) preliminarily investigate the mechanism by which exosomes regulate cells on Ti surface. Exosomes secreted by rat BMSCs were collected by ultracentrifugation and analyzed using transmission electron microscopy and nanoparticle tracking analysis. Confocal fluorescence microscopy, scanning electron microscopy, cell counting kit 8 (CCK8), quantitative real-time polymerase chain reaction techniques and Alkaline Phosphatase bioactivity, Alizarin Red staining and quantification were used to investigate the exosomes that adhere to the Ti plates under different treatments as well as the morphological change, adhesion, spread, and differentiation of BMSCs. We found that exosomes were efficiently internalized and could regulate cell morphology and promoted the adhesion, spreading, and osteogenic differentiation of BMSCs. These were achieved partly by activating the RhoA/ROCK signaling pathway. Our discovery presents new insight into the positive regulatory effect of exosomes on the biological behaviors of BMSCs on Ti surface and provides a novel route to modify the surface of a Ti implant.